THE EFFECTIVITY OF STAKEHOLDERS’ COLLABORATION ON TOURISM DESTINATION GOVERNANCE IN PANGANDARAN, WEST JAVA, INDONESIA - Putro, Heru Purboyo Hidayat; Briliayanti, Astri (ITB Journal Publisher, LPPM ITB, 2019)
In 2010, the concept of destination management organization (DMO) was applied as an effort to improve the weakness of tourism management in Pangandaran. This concept stresses the form of collaboration among stakeholders who are involved in tourism from community groups, private sectors, and government. The stakeholders are led by a destination management organization: Forum Tata Kelola Pariwisata (FTKP/Pangandaran Tourism Governance Forum) which serves as a mediator, facilitator, and coordinator for the three groups of stakeholders. This research was conducted using a case study approach which was deliberately applied to a Pangandaran Village. Besides, this research also employed a mix method approach that practically combines quantitative and qualitative research methods aimed to find out the effectivity of stakeholders? collaboration in implementing the concept of DMO in Pangandaran. The results of this research show that collaboration among stakeholders in DMO-based tourism destination governance has run quite effectively. This is manifested by the existence of common goals, equality, and high commitment from stakeholders. FTKP leadership is fairly good to support collaboration among stakeholders. However, trust and communication among stakeholders need to be improved.